A Matter of Class: Taxonomies of Religion - Smith, Jonathan Z. (Harvard theological review, 1996)
As Robin Winks has persistently and wittily demonstrated, there are striking and suggestive parallels between the methods of scholarship, especially in the human sciences, and detective fiction. Perhaps the earliest self-conscious methodologist, therefore, is the redoubtable Sherlock Holmes. Some attention has been given to extracting his procedures and presuppositions from the prosaic, once-removed accounts of Dr. Watson, who plays a role in Doyle's fictions somewhere between one of Socrates' interlocutors, “I hadn't thought of that, please continue” and Jesus' disciples as represented by Mark, who, in one scholar's well-known formulation, progress from “nonunderstanding to misunderstanding.” In the literature on Holmes, however, I find surprisingly little attention paid to the manuscript writings and publications by the archetypical detective himself. There are fourteen in all, although four seem only sketches. While the two “memoirs” Holmes published in the Anthropological Journal are attractive, it is what appears to be his first publication, one of three translated into French, that catches my eye. Holmes describes this publication, which is primarily concerned with tobacco ashes, in The Sign of the Four.